2016
DOI: 10.1021/acs.jmedchem.5b01599
|View full text |Cite
|
Sign up to set email alerts
|

Development of Autotaxin Inhibitors: An Overview of the Patent and Primary Literature

Abstract: The autotaxin-lysophophatidic acid (ATX-LPA) signaling pathway is implicated in a variety of human disease states including angiogenesis, autoimmune diseases, cancer, fibrotic diseases, inflammation, neurodegeneration, and neuropathic pain, among others. As a result, ATX-LPA has become of significant interest within both the industrial and the academic communities. This review aims to provide a concise overview of the development of novel ATX inhibitors, including the disclosure of the first ATX clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 74 publications
0
83
0
Order By: Relevance
“…Some attempts have been made towards the development of small‐molecule inhibitors of autotaxin, one of which has entered clinical trials . Based on a recent high‐throughput and in silico screening study compound 52 (Figure ) was identified as a potent autotaxin inhibitor with an IC 50 of 117 nM .…”
Section: Pharmacological Activity Of Morpholine Derivatives On Varioumentioning
confidence: 99%
“…Some attempts have been made towards the development of small‐molecule inhibitors of autotaxin, one of which has entered clinical trials . Based on a recent high‐throughput and in silico screening study compound 52 (Figure ) was identified as a potent autotaxin inhibitor with an IC 50 of 117 nM .…”
Section: Pharmacological Activity Of Morpholine Derivatives On Varioumentioning
confidence: 99%
“…The effect of rodent genetic background on weight loss and inflammation associated with ATX deletion obviously needs further investigation, given the broad genetic diversity among humans. In theory, weight loss induced by ATX deletion could potentially be a concern in the development of ATX inhibitors for the treatment of chronic diseases (45). However, it is unlikely that chemical inhibitors achieve .95% inhibition of ATX activity, which, by inference, is associated with the weight loss observed in the current study.…”
Section: Discussionmentioning
confidence: 72%
“…Activity-based lead discovery campaigns, using artificial substrates as activity reporters, subsequently made important contributions, many of which are reviewed in e.g. [35,36]. The structural characterization of rat and mouse ATX structures in 2011 [24,26], enabled a remarkable potential for selective inhibitor design by focusing on the three dimensional architecture of the ATX active site.…”
Section: The Autotaxin Inhibitor Familymentioning
confidence: 99%